2016
DOI: 10.1007/s40626-016-0057-7
|View full text |Cite
|
Sign up to set email alerts
|

Grapevine adaptations to water stress: new perspectives about soil/plant interactions

Abstract: Grapevine adaptations to water-stress are described, by focusing on soil/root interactions and root-to-shoot signaling to control both plant water relations and fruit ripening process.Root response to drought, tolerance of available rootstock germoplasm, mechanisms of embolism formation and repair in root, aquaporin control of plant water relations, and abscisic acid biosynthesis and delivery are highlighted, by reviewing recent insights coming from either (eco)physiological literature or viticultural assays a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
61
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 93 publications
5
61
0
1
Order By: Relevance
“…Management of cover crops and mulching can contribute to reducing vineyard water consumption (Medrano et al, 2015). The choice of plant material is a very powerful tool to adapt vineyards to drought, through the combination of drought-resistant rootstocks (Ollat et al, 2016) and drought-resistant cultivars (Lovisolo et al, 2016;Schultz, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Management of cover crops and mulching can contribute to reducing vineyard water consumption (Medrano et al, 2015). The choice of plant material is a very powerful tool to adapt vineyards to drought, through the combination of drought-resistant rootstocks (Ollat et al, 2016) and drought-resistant cultivars (Lovisolo et al, 2016;Schultz, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Some crops show high sensitivity to current natural UV-B levels, while others express great tolerance to enhanced doses (Teramura & Sullivan, 1991). For these reasons, and due to the great diversity of physiological and biochemical characteristics among varieties (Zarrouk et al, 2016), as well as the high plasticity and adaptive capacity found under different growing conditions (Lovisolo et al, 2016;, it is worthwhile to investigate grapevine responses to multiple environmental stresses influencing crop performances under natural conditions. Several morphogenic mechanisms allow plants to cope with high temperature and sunlight levels during the different phenological stages (Cramer, 2010;Potters et al, 2006) in order to reduce negative impacts on growth and production.…”
Section: Introductionmentioning
confidence: 99%
“…The stomatal control over transpiration is particularly sensitive to abiotic stresses (Düring, 1998;Soar, 2006;Fernandes de Oliveira & Nieddu, 2016b). Due to the combination of varietal differences in hydraulic properties and cellwall elasticity with hormonal signals, leaf gas exchange performance may vary greatly among cultivars, depending upon the growing conditions of the site (Hugalde & Vila, 2018;Lovisolo et al, 2016). Nevertheless, the differences in stomatal regulation under drought conditions among the varieties studied to date make it possible to classify them as near-isohydric (pessimistic) or near-anisohydric (optimistic) (Schultz, 2003;Dal Santo et al, 2016;Zarrouk et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Severe water stress, however, leads to reduced gas exchange (photosynthesis and transpiration) through stomatal and hydraulic controls (probably sustained by a chemical signal, ABA), consequently decreasing early plant growth (Dry et al, 2000a,b;Chaves et al, 2010). The stomatal regulation of transpiration, together with a reduction in vessel hydraulic conductivity, tends to optimize water use efficiency, while reducing the risk of physiological disorders, such as embolism in vessels during severe drought (Lovisolo et al, 2016). By limiting water flow throughout the plant, and thus limiting canopy development (decreasing leaf area by leaf fall), the plant is able to maintain leaf water potentials above threshold values, thus avoiding the onset of cavitation (the appearance of air bubbles in vessels) under high water deficit conditions (Tyree and Sperry, 1988).…”
Section: Introductionmentioning
confidence: 99%